2021
DOI: 10.1249/mss.0000000000002684
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Adaptive Responses to Different Types of Short-Term Exercise Training and Detraining in Middle-Age Men

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Intuitively, this may be due to the relative specificity of recruiting large muscle groups of the lower extremity necessary for pedaling [ 20 , 81 ] and resistance imposed by increases in cycle ergometer wattage/power output that are distinct from the gravitational forces imposed by running. Heydari et al [ 51 ] similarly observed significant increases in FFM following 12 weeks of HIIT in young males, while we have also demonstrated 6 weeks of cycle ergometer HIIT to significantly increase lean mass (1.0 kg), albeit in conjunction with a high protein diet [ 82 ]. More research is required on the possible mechanism of enhanced cycling-induced FFM improvements during HIIT compared to other modalities before definitive conclusions may be reached.…”
Section: Discussionsupporting
confidence: 51%
“…Intuitively, this may be due to the relative specificity of recruiting large muscle groups of the lower extremity necessary for pedaling [ 20 , 81 ] and resistance imposed by increases in cycle ergometer wattage/power output that are distinct from the gravitational forces imposed by running. Heydari et al [ 51 ] similarly observed significant increases in FFM following 12 weeks of HIIT in young males, while we have also demonstrated 6 weeks of cycle ergometer HIIT to significantly increase lean mass (1.0 kg), albeit in conjunction with a high protein diet [ 82 ]. More research is required on the possible mechanism of enhanced cycling-induced FFM improvements during HIIT compared to other modalities before definitive conclusions may be reached.…”
Section: Discussionsupporting
confidence: 51%
“…Similar to the results of recent studies, the within-group analyses revealed that HIIT and MICT achieve a significant decrease in the FM of the young and middle-aged. With regards to FFM, no positive effects were found in both the HIIT and MICT groups, as the results of a network meta-analysis [ 75 ] indicated that resistance training might be the best exercise form for improving FFM [ 93 ]. Although our results showed that HIIT is more significant in PFM reduction than MICT (even though the improvement was small), no statistical differences were found between HIIT and MICT in FM and FFM improvement in the participants.…”
Section: Discussionmentioning
confidence: 99%
“…EIMI is a widespread concern in athletes. Improvement of physiological muscle receptivity and optimizing training intensity may avoid severe permanent injury 21,22 . There is a tremendous significance and clinical value in exploring the characteristics of temporal changes in skeletal muscle physiopathology in response to various levels of exercise.…”
Section: Discussionmentioning
confidence: 99%